Progression to cancer in patients with confirmed dysplasia compared to dysplasia downgraded to non-dysplastic metaplasia in Barrett’s esophagus: a retrospective cohort study in Sweden - Peter Elbe; Åke Öst; Lennart Mellbom; Anders Thorell; Bengt Håkanson; Fredrik Klevebro; Mats Lindblad (Clinical Endoscopy)
Background/Aims This study aimed to clarify the risk of progression in patients with non-dysplastic Barrett’s esophagus (NDBE) and patients with confirmed low-grade dysplasia (LGD) and indefinite for dysplasia (IND) after an expert pathologist review of patients with BE with suspected dysplasia in a prospective cohort. Methods Patients with Barrett’s esophagus diagnosed with dysplasia at Ersta Hospital in Stockholm from 1998 to 2012 were included. The first dysplastic specimen in all patients was re-evaluated by two expert pathologists and classified as NDBE, LGD, IND, or cancer, including high-grade dysplasia. The incidence rates (IRs) and IR ratios were calculated with 95% confidence intervals. Results Of 423 patients with Barrett’s esophagus with dysplasia, 266 (62.9%) were re-classified as NDBE, 83 (19.6%) had LGD, 71 (16.8%) had IND, and 3 (0.7%) patients had cancer. During the follow-up, 34 (8%) patients developed cancer, most of them within five years, while others progressed after up to 25 years of surveillance. IRs for cancer among patients with NDBE was 0.41%/year compared to 1.84%/year for LGD (p<0.001) and 1.43%/year for IND (p=0.008). Conclusions Long-term risk of progression to cancer did not differ between patients with confirmed LGD and IND. These findings suggest that patients with IND should undergo similar management as patients with LGD.